Polyvinyl alcohol composition, polyvinyl alcohol film and method for producing the same and use thereof

By using a combination of polyols and tetrafluoroborate ionic liquids, the problems of plasticizer migration and glycerol spots were solved, thereby improving the optical and mechanical properties of polyvinyl alcohol films.

CN122127719APending Publication Date: 2026-06-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411752805.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2026-06-02

AI Technical Summary

Technical Problem

Existing polyvinyl alcohol films suffer from plasticizer migration and seepage during use, leading to a decline in optical and mechanical properties. Furthermore, glycerol spots are easily formed during heat treatment, affecting film quality.

Method used

A polyvinyl alcohol composition containing polyols and tetrafluoroborate ionic liquid is used. The polyols are firmly bound between molecular chains by hydrogen bonding and electrostatic forces. Combined with the thermal stability of the ionic liquid, the migration and precipitation of plasticizers are inhibited.

Benefits of technology

It improves the optical and mechanical properties of polyvinyl alcohol films, avoids performance degradation caused by plasticizer precipitation, and reduces the formation of glycerol spots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165419010000041
    Figure BDA0005165419010000041
  • Figure BDA0005165419010000081
    Figure BDA0005165419010000081
  • Figure BDA0005165419010000091
    Figure BDA0005165419010000091
Patent Text Reader

Abstract

This invention relates to the field of polymer materials, and discloses a polyvinyl alcohol composition, a polyvinyl alcohol film, a method for preparing the same, and their applications. The polyvinyl alcohol composition comprises polyvinyl alcohol resin, a plasticizer, and a surfactant; the plasticizer comprises a polyol and a tetrafluoroborate ionic liquid. This PVA film exhibits higher residual plasticizer content and tensile strength, resulting in polarizers with higher transmittance and polarization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials, specifically to a polyvinyl alcohol composition, a polyvinyl alcohol film, and their preparation methods and applications. Background Technology

[0002] Currently, the production method of polyvinyl alcohol (PVA) optical films involves dissolving washed PVA resin, additives, and surfactants, followed by processes such as degassing, die casting, drying on drying rollers, heat treatment in an air flotation oven, and winding to obtain the finished PVA optical film. PVA optical films are mainly used in the production of polarizers, with the end product being various types of liquid crystal displays. The performance of the PVA optical film determines the optical properties of the polarizer, such as polarization degree and transmittance. PVA optical films are further swelled, dyed, stretched, and fixed, and then laminated with cellulose triacetate (TAC) films to form polarizers.

[0003] Glycerol, a plasticizer in PVA films, migrates and seeps out during use, causing the film to soften and become sticky. The PVA film, having lost its plasticizer, shrinks and hardens. Simultaneously, the migrated plasticizer dissolves in the aqueous bath during subsequent stretching and dyeing processes, reducing the plasticizer content in the PVA film and leading to a decrease in its optical properties and elongation. Furthermore, during heat treatment, due to significant temperature changes, glycerol tends to accumulate at the air flotation oven nozzles and internal / external joints, forming glycerol droplets. These droplets create glycerol spots on the film surface, significantly degrading the film's optical properties.

[0004] To address the above issues, CN1168901A proposes mixing ethylene oxide with a polyol compound containing 3 to 6 hydroxyl groups via an addition reaction to prepare polyvinyl alcohol (PVA) films. However, the ethylene oxide used in this invention is a toxic gas, and residual raw materials can affect subsequent film preparation. CN104356569A proposes using cyclodextrin and polyol compounds as plasticizers to prepare PVA films. However, the cyclodextrin used in this invention has relatively low solubility in aqueous solutions, affecting subsequent film processing. CN107141380A proposes adding a quantitative amount of plasticizer during polymerization and / or alcoholysis to obtain a PVA product containing plasticizer. However, this invention does not address the issue of glycerol migration and droplet formation during use. Summary of the Invention

[0005] To overcome the problem of plasticizer migration and exudation in existing technologies, this invention provides a polyvinyl alcohol film, its preparation method, and its application, which can inhibit plasticizer migration and exudation, avoid the formation of plasticizer oil spots, and improve the optical and mechanical properties of the polyvinyl alcohol film.

[0006] To achieve the above objectives, a first aspect of the present invention provides a polyvinyl alcohol composition comprising a polyvinyl alcohol resin, a plasticizer, and a surfactant;

[0007] The plasticizer comprises a polyol and a tetrafluoroborate ionic liquid.

[0008] A second aspect of the present invention provides a method for preparing a polyvinyl alcohol film, comprising the following steps:

[0009] (1) The composition provided in the first aspect of the present invention is mixed with a solvent to obtain a casting solution;

[0010] (2) The casting solution is degassed, shaped, dried and heat-treated to obtain a polyvinyl alcohol film.

[0011] A third aspect of the present invention provides a polyvinyl alcohol film prepared by the method described in the second aspect of the present invention.

[0012] The fourth aspect of the present invention provides a composition provided in the first aspect of the present invention, or the application of a polyvinyl alcohol film provided in the third aspect of the present invention in a polarizer.

[0013] The beneficial effects of this invention are as follows:

[0014] In the polyvinyl alcohol film prepared by the polyethylene composition provided by the present invention, the tetrafluoroborate ionic liquid can firmly bind the polyol between the molecular chains through hydrogen bonding and electrostatic forces, preventing it from migrating; at the same time, due to the good thermal stability of the ionic liquid itself, it can also reduce the precipitation of plasticizers during heat treatment, thereby avoiding the decline in the optical and mechanical properties of the polyvinyl alcohol film caused by the precipitation of plasticizers. Detailed Implementation

[0015] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0016] A first aspect of the present invention provides a polyvinyl alcohol composition comprising a polyvinyl alcohol resin, a plasticizer, and a surfactant;

[0017] The plasticizer comprises a polyol and a tetrafluoroborate ionic liquid.

[0018] In this invention, tetrafluoroborate ionic liquid can firmly bind polyols between polyvinyl alcohol molecular chains through hydrogen bonding and electrostatic forces, preventing them from migrating. At the same time, due to the good thermal stability of the ionic liquid itself, it can also reduce the precipitation of polyols during heat treatment, thereby avoiding the decline in the optical and mechanical properties of polyvinyl alcohol films caused by polyol precipitation.

[0019] According to the present invention, preferably, the degree of polymerization of the polyvinyl alcohol resin is 1600-2500 and the degree of hydrolysis is 95-99.9%.

[0020] In this invention, when the degree of polymerization and degree of hydrolysis of the polyvinyl alcohol resin are within the above-mentioned range, the prepared polyvinyl alcohol film has better optical and mechanical properties.

[0021] More preferably, the degree of polymerization of the polyvinyl alcohol resin is 2000-2400, and the degree of hydrolysis is 98-99.9%.

[0022] According to a preferred embodiment of the present invention, the mass ratio of the polyvinyl alcohol resin, plasticizer and surfactant is 100:10-25:0.05-1.

[0023] In this invention, when the mass ratio of the polyvinyl alcohol resin, plasticizer, and surfactant is within the above-mentioned range, the film prepared from the polyvinyl alcohol composition has better optical and mechanical properties.

[0024] More preferably, the mass ratio of the polyvinyl alcohol resin, plasticizer, and surfactant is 100:5-30:0.05-3.

[0025] According to a preferred embodiment of the present invention, the mass ratio of the polyol to the tetrafluoroborate ionic liquid is 30-50:1.

[0026] In this invention, when the mass ratio of the polyol to the tetrafluoroborate ionic liquid is within the above-mentioned range, the migration and precipitation of the polyol can be better suppressed, thereby further improving the optical and mechanical properties of the polyvinyl alcohol film.

[0027] The mass ratio of the polyol to the tetrafluoroborate ionic liquid can be 30:1, 35:1, 40:1, 45:1, 50:1, or any range between the two.

[0028] More preferably, the mass ratio of the polyol to the tetrafluoroborate ionic liquid is 35-45:1.

[0029] According to a preferred embodiment of the present invention, the cation of the tetrafluoroborate ionic liquid is selected from...

[0030] At least one of them, wherein R, R1 and R2 are each independently selected from H or alkyl.

[0031] The alkyl group can be a C1-C8 straight-chain, branched, cyclic aliphatic alkyl group or aralkyl group, preferably ethyl or n-propyl.

[0032] In this invention, when the cation of the tetrafluoroborate ionic liquid is selected from the above-mentioned range, it has better compatibility with polyols.

[0033] More preferably, the cation of the tetrafluoroborate ionic liquid is

[0034] In this invention, the anion of the tetrafluoroborate ionic liquid is...

[0035] According to a specific embodiment of the present invention, the tetrafluoroborate ionic liquid is selected from 1-ethyl-3-methylimidazolium tetrafluoroborate, n-butylpyridine tetrafluoroborate and 1-propyl-3-methylimidazolium tetrafluoroborate.

[0036] According to a preferred embodiment of the present invention, the polyol is selected from C 10 The following polyols.

[0037] In this invention, when the polyol is selected from the above range, it has better compatibility with ionic liquids.

[0038] More preferably, the polyol is selected from at least one of ethylene glycol, propylene glycol, glycerol, and butanediol.

[0039] More preferably, the polyol is glycerol.

[0040] According to a preferred embodiment of the present invention, the surfactant comprises anionic surfactant and / or nonionic surfactant.

[0041] The anionic surfactant can be an ether sulfate and / or an acyl amino acid.

[0042] The nonionic surfactant may be fatty acid alcohol amide, fatty alcohol polyoxyethylene ether, and / or alkylphenol polyoxyethylene ether.

[0043] More preferably, the surfactant is lauric acid diethanolamide and / or sodium lauryl ether sulfate.

[0044] According to the present invention, preferably, the hydrophilic-lipophilic balance value of the surfactant is 10-14.

[0045] In this invention, when the hydrophilic-lipophilic balance value of the surfactant is within the above-mentioned range, the surfactant can make the polyol and tetrafluoroborate ionic liquid more uniformly dispersed in the polyvinyl alcohol resin, while inhibiting the precipitation of polyol, thereby further improving the flexibility and optical properties of the polyvinyl alcohol film.

[0046] More preferably, the surfactant has a hydrophilic-lipophilic balance value of 10-12.

[0047] A second aspect of the present invention provides a method for preparing a polyvinyl alcohol film, comprising the following steps:

[0048] (1) The composition provided in the first aspect of the present invention is mixed with a solvent to obtain a casting solution;

[0049] (2) The casting solution is degassed, shaped, dried and heat-treated to obtain a polyvinyl alcohol film.

[0050] In the above method, the precipitation of polyol can be suppressed by the synergistic effect of polyol and tetrafluoroborate ionic liquid, thereby improving the optical and mechanical properties of the prepared polyvinyl alcohol film.

[0051] The present invention does not particularly limit the specific type of solvent, and those skilled in the art can choose conventionally. According to the present invention, preferably, the solvent is selected from at least one of water, ethanol, isopropanol, acetone, dimethyl sulfoxide, and N,N-dimethylformamide.

[0052] More preferably, the solvent is water.

[0053] According to a preferred embodiment of the present invention, the solvent content in the casting solution is 60-90 wt%.

[0054] The present invention does not particularly limit the specific method of degassing, and those skilled in the art can choose conventional methods. For example, the degassing method can be vacuum degassing, ultrasonic degassing, static degassing, stirring degassing, or heating degassing.

[0055] According to the present invention, preferably, the mixing temperature in step (1) is 100-150°C and the time is 5-10h.

[0056] In this invention, when the mixing temperature and time in step (1) are within the above range, the mixing is more uniform and the plasticizing effect is better.

[0057] More preferably, the mixing temperature in step (1) is 120-140°C and the time is 6-8h.

[0058] According to the present invention, preferably, the drying temperature in step (2) is 50-100°C and the time is 5-30 min.

[0059] In this invention, when the drying temperature and time in step (2) are within the above range, the moisture content of the pre-wound film can be better controlled, thus ensuring the heat treatment effect.

[0060] More preferably, the drying temperature in step (2) is 60-80°C and the time is 15-25 min.

[0061] According to the present invention, preferably, the heat treatment temperature in step (2) is 100-150°C and the time is 2-10 min.

[0062] In this invention, when the temperature and time of the heat treatment in step (2) are within the above range, the thermodynamic properties of the thin film are better.

[0063] More preferably, the heat treatment temperature in step (2) is 110-140°C and the time is 4-8 min.

[0064] A third aspect of the present invention provides a polyvinyl alcohol film prepared according to the method described in the second aspect of the present invention.

[0065] The fourth aspect of the present invention provides a composition provided in the first aspect of the present invention, or the application of a polyvinyl alcohol film provided in the third aspect of the present invention in a polarizer.

[0066] The polarizer prepared by the polyvinyl alcohol film provided by the present invention has a plasticizer residue of ≥90%, tensile strength of ≥80MPa, elongation at break of ≥440%, transmittance of ≥43%, and polarization of ≥99.2%.

[0067] The present invention also provides a method for preparing a polarizer, the method comprising the following steps:

[0068] (1) Immerse the polyvinyl alcohol film in water for 10-30 seconds;

[0069] (2) Immerse the polyvinyl alcohol film treated in step (1) in an iodine / potassium iodide aqueous solution for 1-5 min, wherein the mass concentration ratio of iodine to potassium iodide in the iodine / potassium iodide aqueous solution is 1:50-200;

[0070] (3) The polyvinyl alcohol film treated in step (2) is uniaxially stretched to 4-8 times its original length in the first boric acid aqueous solution at a stretching rate of 8-15 m / min. The boric acid concentration in the first boric acid aqueous solution is 30-50 g / L.

[0071] (4) Immerse the polyvinyl alcohol film treated in step (3) in a potassium iodide aqueous solution for 3-10 min, wherein the potassium iodide concentration in the potassium iodide aqueous solution is 40-80 g / L;

[0072] (5) Immerse the polyvinyl alcohol film treated in step (4) in a second boric acid aqueous solution for 3-10 min;

[0073] (6) The polyvinyl alcohol film treated in step (5) is dried with hot air at a temperature of 50-60°C for 3-10 minutes. The boric acid concentration in the second boric acid aqueous solution is 30-50 g / L.

[0074] (7) Attach cellulose triacetate film to both sides of the polyvinyl alcohol film treated in step (6) to obtain a polarizer.

[0075] In the above method for preparing polarizers, the temperatures of water and aqueous solutions are each independently 25-40℃.

[0076] In the polarizer, preferably, the polyvinyl alcohol film has a thickness of 10-40 μm and the cellulose triacetate film has a thickness of 20-50 μm.

[0077] In this invention, the tensile strength and elongation at break of the polyvinyl alcohol film were determined in accordance with GB / T12683-2009.

[0078] The glycerol content of the polyvinyl alcohol film was determined by iodometric titration, as follows:

[0079] Weigh 60g of sodium periodate (NaIO4) and place it in a beaker. Add 120mL of standard sulfuric acid titration solution [c(1 / 2H2SO4)=0.1000mol / L] and a small amount of water to dissolve it. Heating is not allowed during dissolution. If the solution is not clear, filter it with a sintered glass funnel (do not use filter paper). Transfer the solution to a 1000mL volumetric flask and dilute to the mark.

[0080] Mix 50 mL of ethylene glycol (analytical grade) with 50 mL of distilled water, add 5 drops of bromothymol blue indicator solution (1 g / L), and titrate with sodium hydroxide standard titration solution [c(NaOH)=0.1000mol / L] until the solution turns blue. Prepare before use.

[0081] Standard titration solution of sodium hydroxide: c(NaOH) = 0.1000 mol / L.

[0082] Sulfuric acid standard titration solution: c(1 / 2H2SO4)=0.1000mol / L.

[0083] Bromothymol blue indicator solution: 1 g / L ethanol solution.

[0084] Weigh (1.0±0.1) g of the sample into a stoppered conical flask, add about 200 mL of distilled water, and stir on a magnetic stirrer at 180 °C and 400 rpm until completely dissolved.

[0085] Add 5 drops of bromothymol blue indicator solution (1 g / L). The solution should be green or yellowish-green. If the solution is blue-green, titrate with standard sulfuric acid solution [c(1 / 2H₂SO₄) = 0.1000 mol / L] until the solution is green or yellowish-green, then titrate with standard sodium hydroxide solution [c(NaOH) = 0.1000 mol / L] until the solution is pure blue. Add 10 mL of sodium periodate solution, shake gently, stopper the bottle, and place in the dark for 30 minutes (temperature should not exceed 35℃). Add 10 mL of neutral ethylene glycol solution, place in the dark for 20 minutes, and titrate with standard sodium hydroxide solution [c(NaOH) = 0.1000 mol / L] until the solution is pure blue. Perform a blank test simultaneously.

[0086] The glycerol content is calculated using the following formula:

[0087]

[0088] In the formula:

[0089] X 丙三醇 —Percentage content of glycerol, %.

[0090] V1—The volume of sodium hydroxide standard titration solution consumed by the sample, in mL;

[0091] V0—The volume of sodium hydroxide standard titration solution consumed in the blank test, in mL;

[0092] c—Concentration of the sodium hydroxide standard titration solution, mol / L;

[0093] 0.09209 — the mass of glycerol, expressed in grams, equivalent to 1.00 mL of a standard sodium hydroxide titration solution [c(NaOH) = 1.000 mol / L];

[0094] m — mass of the sample, in grams.

[0095] The transmittance of the polarizer is determined as follows:

[0096] Using the stretching direction (i.e., optical axis) of the PVA film as the reference edge, the polarizer was cut into 40mm×40mm pieces along the 45° direction. The transmittance was calculated by using a Shimadzu UV 2200 spectrophotometer and referring to GB / T25275-2010, by averaging the values ​​in the 45° and -45° directions relative to the stretching axis of the polarizer.

[0097] The polarization degree of the polarizer is measured in the following manner:

[0098] Using the stretching direction (i.e., optical axis) of the PVA film as the reference edge, the polarizer is cut into two 40mm × 40mm pieces at a 45° angle. The two cut polarizer pieces are overlapped in a manner parallel to the polarization axis, and the transmittance of the overlapped polarizer is measured using a Shimadzu UV 2200 spectrophotometer, denoted as parallel transmittance Y1. The two cut polarizer pieces are overlapped in a manner orthogonal to the polarization axis, and the transmittance of the overlapped polarizer is measured, denoted as orthogonal transmittance Y2. The polarization degree V of the polyvinyl alcohol polarizer is calculated according to the following formula.

[0099]

[0100] The glycerol spot on the polarizing film is evaluated as follows:

[0101] Using the stretching direction of the PVA film (i.e., the optical axis) as the reference edge, the polarizer is cut into 40mm×40mm pieces along the 45° direction and sandwiched at a 45° angle between two polarizers in orthogonal Nicol configuration (each with a transmittance of 43.5% and a polarization of 99.9%). In a darkroom, a light box with a surface illuminance of 14000lx is used to observe whether there are glycerol spots in the transmission mode.

[0102] The present invention will be described in detail below through embodiments.

[0103] Unless otherwise specified, all raw materials and reagents used in the following examples are commercially available.

[0104] The cellulose triacetate membrane was purchased from FIXFILM and was 40 μm thick.

[0105] The PVA resin has a degree of polymerization of 2200 and a degree of alcoholysis of 99.5%.

[0106] Examples 1-13

[0107] Following the feed amounts shown in Table 1, PVA resin, glycerol, 1-ethyl-3-methylimidazolium tetrafluoroborate, and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a mass concentration of 15%. After the casting solution was allowed to stand for 7 hours to remove bubbles, it was cast using a die and dried for 10 minutes using 10 drying rollers with a surface temperature of 75°C. Then, it was heat-treated at 120°C for 5 minutes and wound up using a winding machine to obtain a PVA film.

[0108] Table 1

[0109]

[0110]

[0111] Example 14

[0112] PVA films were prepared according to the raw materials and methods of Example 2, except that 1-ethyl-3-methylimidazolium tetrafluoroborate was replaced with the same mass of n-butylpyridine tetrafluoroborate.

[0113] Example 15

[0114] PVA films were prepared according to the raw materials and methods of Example 2, except that sodium lauryl ether sulfate of the same mass was used instead of diethanolamide lauryl ether.

[0115] Example 16

[0116] PVA films were prepared according to the raw materials and methods of Example 2, except that sodium lauroyl sarcosinate was used instead of diethanolamide lauroate in the same mass.

[0117] Comparative Example 1

[0118] PVA films were prepared according to the raw materials and methods of Example 2, except that 1-ethyl-3-methylimidazolium tetrafluoroborate was not added.

[0119] Comparative Example 2

[0120] PVA films were prepared according to the raw materials and methods of Example 2, except that 1-ethyl-3-methylimidazolium acetate was used instead of 1-ethyl-3-methylimidazolium tetrafluoroborate of the same mass.

[0121] Comparative Example 3

[0122] PVA films were prepared according to the raw materials and methods of Example 2, except that 1-ethyl-3-methylimidazolium tetrafluoroborate was replaced with the same mass of 1,3-dimethylimidazolium phosphate.

[0123] Application examples

[0124] PVA films prepared in the above examples and comparative examples were pre-swelled by immersing in water at 30°C for 20 seconds, and then immersed in an I2 / KI aqueous solution (total I2 and KI concentration 3.5 g / L, I2 to KI mass ratio 1:100) at 35°C for 3 minutes for staining. The stained PVA films were uniaxially stretched to 6 times their original length at a rate of 10 m / min in a 40 g / L boric acid aqueous solution at 50°C. The stained and stretched PVA films were then immersed in a 60 g / L KI aqueous solution at 30°C for 5 minutes, and then in a 35 g / L boric acid aqueous solution at 30°C for 5 minutes. The PVA films were then removed and dried with hot air at 55°C for 6 minutes to obtain a PVA film with a thickness of 30 μm. Finally, a 40 μm thick cellulose triacetate film was attached to both sides of the PVA film to obtain a polarizer.

[0125] Test case

[0126] The residual plasticizer content, tensile strength, transmittance, and polarization of the stretched and dyed PVA film were tested according to the method described in the specific embodiments of this invention. The results are shown in Table 2.

[0127] Table 2

[0128]

[0129]

[0130] As can be seen from the results in Table 2, the PVA film provided by the present invention has higher residual plasticizer content and tensile strength, and the polarizer prepared using the PVA film provided by the present invention has higher transmittance and polarization.

[0131] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A polyvinyl alcohol composition, characterized in that, It contains polyvinyl alcohol resin, plasticizer, and surfactant; The plasticizer comprises a polyol and a tetrafluoroborate ionic liquid.

2. The composition according to claim 1, characterized in that, The mass ratio of the polyvinyl alcohol resin, plasticizer, and surfactant is 100:10-25:0.05-1.

3. The composition according to claim 1, characterized in that, The mass ratio of the polyol to the tetrafluoroborate ionic liquid is 30-50:

1.

4. The composition according to claim 1, characterized in that, The cations of the tetrafluoroborate ionic liquid are selected from... At least one of them, wherein R, R1 and R2 are each independently selected from H or alkyl.

5. The composition according to any one of claims 1-4, characterized in that, The polyol is selected from C 10 The following polyols; Preferably, the polyol is selected from at least one of ethylene glycol, propylene glycol, glycerol, and butanediol.

6. The composition according to any one of claims 1-4, wherein the surfactant comprises anionic surfactant and / or nonionic surfactant.

7. A method for preparing a polyvinyl alcohol film, characterized in that, Includes the following steps: (1) Mix the composition according to any one of claims 1-6 with a solvent to obtain a casting solution; (2) The casting solution is degassed, shaped, dried and heat-treated to obtain a polyvinyl alcohol film.

8. The method according to claim 7, characterized in that, The solvent content in the casting solution is 60-90 wt%. Preferably, the mixing temperature in step (1) is 100-150℃ and the time is 5-10h; Preferably, the drying temperature in step (2) is 50-100℃ and the time is 5-30 min; Preferably, the heat treatment temperature in step (2) is 100-150℃ and the time is 2-10 min.

9. A polyvinyl alcohol film prepared by the method of claim 7 or 8.

10. The composition according to any one of claims 1-6, or the use of the polyvinyl alcohol film according to claim 9 in a polarizer.

Citation Information

Patent Citations

  • Polyvinyl alcohol (PVA) film and preparation method thereof, and polaroid

    CN104356569A

  • Preparation method of raw material PVA for production of polyvinyl alcohol optical film

    CN107141380A